Visible light photocatalytic activity of Mn-doped BiFeO3 nanoparticles. Issue 1 (2nd January 2020) - Ponraj, Caroline; Vinitha, G.; Daniel, Joseph
ABSTRACT: The discharges of effluents from the Textile industries contain bleaching and dyeing chemicals which are very harmful to the environment. Thus, managing textile effluents to make zero discharge of the above chemicals using renewable energy is the need of the hour. Here we report photocatalytic degradation of Acid Red-85, textile dye in visible light by energy bandgap optimized magnetic nanoparticles. The BiFe1-x Mnx O3 (x = 0, 0.025, 0.05, 0.075 & 0.1) nanoparticles were synthesized by citrate gel auto-ignition method. The synthesized compounds show well-defined crystalline particles with decrease of crystallite size from 57 to 20 nm with increase of Mn 2+ concentration. All samples show well-separated particle morphology with decrease of average particle size with increase of manganese concentration. Optical absorption studies reveal that the energy band-gap of sample decreases from 2.2 to 1.97 eV with increase of Mn ions in BiFeO3 lattice. The coercive field (Hc ) and remnant magnetization (Mr ) enhance up to 5% of manganese content and then reduces with further increase of dopant concentration due to hindrance of magnetic exchange in Mn-O-Fe network. Manganese doping helps in increasing the degradation efficiency of BiFeO3 nanoparticles and the rate constant (K) increases from 2.6 × 10 −2 to 6.84 × 10 −2 min −1 respectively. It is attributed to long charge separation time in doped samples which is confirmed by photoluminescence spectrum. Mn-doped BiFeO3 has an edge over the widely studied TiO2 and ZnO because of its absorbance in visible light spectrum and its ability to be magnetically removed after treatment.